Faktor-Faktor Yang Memengaruhi Minat Penggunaan Social Commerce Pada Generasi-Z Menggunakan Pendekatan Modified Technology Accepted Model (TAM) - Andini Amalia Puspitasari; Zaki Baridwan (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2026)
This study quantitatively examines the factors affecting Generation-Z intention to use Social Commerce based on a modified Technology Accepted Model (TAM) approach. The samples include 275 respondents of social commerce users who are Accounting Undergraduate students of FEB UB Class of 2020—2022 aged 18-25 years, selected through purposive sampling. The data are collected through survey distributed via google form, and analyzed by Partial Least Square (PLS) processed by the SmartPLS software. The results of this study exhibit that perceived ease of use, perceived usefulness and perceived trust have a positive effect on the Generation-Z intention to use commerce while perceived risk has a negative effect on the Generation-Z intention to use social commerce. The implications of this study is expected to contribute to provide insight to the development of economics and business science as well as social commerce platform to make improvements, innovations and improvements in providing services to customers.